Avaliação da presença de íons na saliva de pacientes em uso de arco lingual com diferentes tipos de soldas - Souza, Helena Reis de (2018)
Objective: Quantify the metal ion release of different brazing and welding methods in the saliva of patients that need a lingual arch appliance and evaluate the surfaces of soldered and welded bands in scanning eléctron microscopy (SEM). Material and Methods: 64 patients were selected and distributed into four groups: Group 1 (21 patients that did not need a lingual arch), group 2 (16 patients that needed a lingual arch and had the appliance manufactured with the silver solder brazing method), group 3 (14 patients that needed a lingual arch and had the appliance manufactured with the laser welding method) and group 4 (13 patients that needed a lingual arch and had the appliance manufactured with the TIG welding method). Saliva samples were collected at different points in time (before treatment, 7 days after placing appliance, 15 days after placing appliance and 30 days after placing appliance) and were analyzed with an ICP mass spectrometer followed by generalized estimating equation modeling with a 5% level of significance. In addition, 9 bands with steel joints were evaluated in SEM to compare the surface of the 3 different joining techniques (brazing, laser welding and TIG welding). Results: For ions Cr, Fe, Cu and Sn comparing concentrations between groups, there was no difference in the variation along the collections and there was no statistically significant difference throughout the collections for any of the groups when comparing these ions concentrations. For Ni, values were compared in groups and at points in time, and an interaction effect was seen (P<0.001). For Zn, Ag, and Cd there was no difference along the points in time. For Zn there was statistic difference from group 4 to groups 1 and 2; for Ag there was statistic difference from group 4 to groups 2 and 3. For Cd there was statistic difference from T1 for T4 in all groups. Digital images were generated and showed different surface characteristics. Brazing presented a flatter and smoother area, while laser and TIG welding developed rougher areas. Conclusions: Orthodontics appliances may affect salivary ion concentrations in vivo over the short term evaluated. For most ions evaluated there was no increasing significant release comparing types of soldering/welding and comparing values throughout the points in time at the same group. Levels resembled those already documented and remained below the daily dietary metals intake. Nevertheless, small amounts of metal ions are able to induce allergic reactions and should be considered. The protocol performed for conventional welding, together with a suitable 7 finishing and polishing, guarantees a more regular welded ring surface. The protocols for laser and TIG welding still have undefined aspects, and the need for filling material must be evaluated to cover irregularities and prevent failures.